Cross-linked polyglutamic acid and cross-linked hyaluronic acid polymer, method for preparing the same, and use thereof in patches
Patent Information
- Application Number
- CN202611001775.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-10-23
AI Technical Summary
(1)本申请提供的交联聚谷氨酸和交联透明质酸聚合物,其中交联聚谷氨酸钠凝胶均匀分散在交联透明质酸钠凝胶中,通过物理嵌合形成蜂窝多孔凝胶,基于多孔结构实现终产品缓慢释放水分的技术效果。
Smart Images

Figure CN122955007A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of medical biomaterials, specifically to a cross-linked polyglutamic acid and cross-linked hyaluronic acid polymer, its preparation method, and its application in dressings. Background Technology
[0002] With the widespread use of laser, radiofrequency, microneedling, mesotherapy, picosecond laser, chemical peels, and superficial plastic surgery, medical aesthetic procedures artificially create controllable superficial skin damage to stimulate collagen regeneration, improve skin texture, and remove pigmentation or scars. The repair process of damaged skin involves a series of dynamic and complex physiological processes, including hemostasis, inflammation control, proliferation, and remodeling. During this repair process, wound dressings are the most important care products, playing a crucial role in wound moisturizing, promoting repair, reducing pain, and controlling inflammation. Among these, patches are currently the most widely used dosage form. Applied to the skin, they reduce moisture evaporation, increase skin permeability, and promote the absorption of active ingredients through local occlusion. Because a certain wound is formed after medical aesthetic procedures, a preservative-free, sterile patch is needed to effectively help replenish moisture to damaged skin, promote wound healing, accelerate skin barrier repair, and reduce post-inflammatory hyperpigmentation, allowing the skin to quickly return to a healthy state.
[0003] Sodium polyglutamate, especially γ-polyglutamate, possesses extremely strong water-retention and water-locking capabilities, exhibiting excellent moisturizing properties. When applied to the skin, it can reduce moisture loss, effectively increase the moisture content of the stratum corneum, resulting in increased skin elasticity, smoothness, and radiance. Polyglutamate's film-forming properties are comparable to hyaluronic acid, but its unique smoothness is something that hyaluronic acid and even collagen lack (Zheng Chao, Research on the Moisturizing Properties of γ-Polyglutamate and Hyaluronic Acid Compound).
[0004] Therefore, we envision using a specific technology to combine sodium hyaluronate and sodium polyglutamate to achieve the aforementioned objective. Existing patent technology, "A Composition Containing Sodium Polyglutamate and its Application in Dressings," discloses dressings composed of sodium polyglutamate, sodium hyaluronate, and collagen of varying molecular weights, combined with other moisturizers, thickeners, and non-woven fabrics, which achieve sterility through freezing (-20°C) followed by irradiation. However, this freezing-and-irradiation method has high costs for large-scale production and poor versatility.
[0005] The sterilization process for aseptic dressings must meet two requirements: firstly, achieving the specified sterility assurance level; and secondly, ensuring the sterilization method is safe and residue-free, while preserving the original function and biosafety of the material to the greatest extent possible. Currently, the most widely used commercial sterilization methods include irradiation sterilization, moist heat sterilization, ethylene oxide sterilization, and filtration sterilization. The choice of different sterilization methods is influenced by various factors such as product dosage form, core biomaterials, sterilization cost, and product packaging materials. This application aims to prepare a moist aseptic dressing, so ethylene oxide sterilization is not feasible. Furthermore, the dressing contains high-molecular-weight polymers such as sodium hyaluronate, making sterilization and filtration difficult to achieve. In our preliminary studies, we prepared mixed solutions of sodium hyaluronate and sodium polyglutamate, as well as single-component solutions, and subjected them to moist heat sterilization at 121°C for 12-15 minutes and room temperature irradiation at 5-10 kGy. We found that irradiation sterilization caused both sodium hyaluronate and sodium polyglutamate to turn yellow and develop an unacceptable odor; moist heat sterilization resulted in some yellowing and a fermented odor in sodium polyglutamate, which was unacceptable to patients. Summary of the Invention
[0006] The first objective of this application is to provide a cross-linked polyglutamic acid and cross-linked hyaluronic acid polymer, wherein the polymer is a physically intercalated gel polymer formed by cross-linked polyglutamic acid and cross-linked hyaluronic acid, wherein the cross-linked polyglutamic acid is obtained by cross-linking polyglutamic acid or its salt with a cross-linking agent, and the cross-linked hyaluronic acid is obtained by cross-linking hyaluronic acid or its salt with a cross-linking agent.
[0007] The polyglutamate salt can be selected from one or more of the sodium, potassium, and zinc salts of polyglutamate, preferably the sodium salt of polyglutamate; the hyaluronic acid salt can be selected from one or more of the sodium, potassium, zinc, calcium, and magnesium salts of hyaluronic acid, preferably the sodium salt of hyaluronic acid.
[0008] The physically cross-linked gel refers to a gel formed through physical forces, such as electrostatic interactions, ionic interactions, hydrogen bonding, and chain entanglement. This application utilizes the electrostatic interactions and hydrogen bonding between two polymers, cross-linked sodium polyglutamate and cross-linked sodium hyaluronate, to form a physically cross-linked cross-linked gel polymer.
[0009] As a biological macromolecule, polyglutamic acid or its salts can be classified into low molecular weight polyglutamic acid or its salts, high molecular weight polyglutamic acid or its salts, and ultra-high molecular weight polyglutamic acid or its salts according to their molecular weight.
[0010] The low molecular weight polyglutamic acid or its salt has a molecular weight of 200kDa-500kDa, for example, 200kDa, 220kDa, 250kDa, 300kDa, 350kDa, 400kDa, 450kDa and 500kDa.
[0011] The high molecular weight polyglutamic acid or its salt has a molecular weight of 800-1500 kDa, for example, 800 kDa, 900 kDa, 1000 kDa, 1050 kDa, 1100 kDa, 1200 kDa, 1300 kDa, 1400 kDa and 1500 kDa.
[0012] The ultra-high molecular weight polyglutamic acid or its salt has a molecular weight of 1800-2500 kDa, for example, 1800 kDa, 1900 kDa, 2000 kDa, 2100 kDa, 2200 kDa, 2300 kDa, 2400 kDa and 2500 kDa.
[0013] The hyaluronic acid or its salt has a molecular weight of 1000-1500 kDa, for example, 1000 kDa, 1100 kDa, 1200 kDa, 1300 kDa, 1400 kDa and 1500 kDa.
[0014] Furthermore, the polyglutamic acid or its salt is selected from high molecular weight polyglutamic acid or its salt and ultra-high molecular weight polyglutamic acid or its salt, or a combination of any two or three polyglutamic acids selected from low molecular weight polyglutamic acid or its salt, high molecular weight polyglutamic acid or its salt and ultra-high molecular weight polyglutamic acid or its salt, preferably a combination of two or three.
[0015] Furthermore, when the polyglutamic acid or its salt is a combination of low-molecular-weight polyglutamic acid or its salt and high-molecular-weight polyglutamic acid or its salt, the mass ratio of the low-molecular-weight polyglutamic acid or its salt to the high-molecular-weight polyglutamic acid or its salt is 1:(0.25-4), preferably 2:3, and the mass ratio of the polyglutamic acid or its salt to the hyaluronic acid or its salt is 1:(0.5-2), preferably 1:1.
[0016] The second objective of this application is to provide a method for preparing the polymer, wherein the polyglutamic acid or its salt is crosslinked with a crosslinking agent to form a polyglutamic acid crosslink, the polyglutamic acid crosslink is added to the hyaluronic acid or its salt, and then a crosslinking agent is added to crosslink, thereby forming the polymer.
[0017] Further, the crosslinking agent is a polyethylene glycol crosslinking agent. Preferably, the molecular weight of the crosslinking agent is 350-1000 Da, for example, 350 Da, 400 Da, 500 Da, 600 Da, 700 Da, 800 Da, 900 Da and 1000 Da. More preferably, the crosslinking agent is polyethylene glycol diglycidyl ether.
[0018] The two-step cross-linking reaction is as follows:
[0019] Furthermore, the mass ratio of polyglutamic acid or its salt to the crosslinking agent in the crosslinked polyglutamic acid is 5:(2-5), preferably 5:3, and the mass ratio of hyaluronic acid or its salt to the crosslinking agent in the crosslinked hyaluronic acid is 5:(1-5), preferably 5:2.
[0020] The third objective of this application is to provide the application of cross-linked polyglutamic acid and cross-linked hyaluronic acid polymers in the preparation of dressings.
[0021] The fourth objective of this application is to provide a sterile dressing comprising a nonwoven fabric and a transparent gel matrix, wherein the transparent gel matrix comprises the cross-linked polyglutamic acid and cross-linked hyaluronic acid polymers.
[0022] Preferably, when the transparent adhesive substrate is 100 parts by weight, the polymer is 20-60 parts by weight; more preferably, the polymer is 50 parts by weight.
[0023] Furthermore, the nonwoven fabric is selected from tensile-resistant nonwoven fabrics, and even further, the elongation at break of the nonwoven fabric in both the transverse and longitudinal directions is greater than 10%, and its main function is as a transparent gel-like matrix carrier, playing a role in sealing and promoting penetration.
[0024] Furthermore, when the transparent gel matrix is 100 parts by weight, the polyol moisturizer is 3-7 parts by weight, the repair agent is 0.2-2 parts by weight, the gelling agent is 0.3-2 parts by weight, and the stabilizer is 0.01-0.2 parts by weight.
[0025] Furthermore, the polyol moisturizer is specifically a combination of two or more of glycerin, pentanediol, propylene glycol, butylene glycol, and hexanediol; the natural polymer moisturizer is the polymer.
[0026] Furthermore, the repair agent is a composition of ectoine, dextran, and allantoin. Allantoin soothes, moisturizes, and increases stratum corneum hydration. Dextran promotes the migration of human keratinocytes (HaCaT) and human skin fibroblasts (HDFa), accelerates wound closure and re-epithelialization, and its anti-inflammatory and anti-irritant properties help relieve inflammation and redness, soothing irritated skin. Further, the dextran is a composition of molecules with molecular weights of 500-2000 kDa and 100-300 kDa. Ectoine has significant anti-inflammatory effects, reducing skin inflammation, relieving redness, and enhancing the damaged skin barrier function.
[0027] Furthermore, the gelling agent is one or a combination of two of the following: carbomer, agarose, xanthan gum, and sodium alginate, wherein the mass fraction of agarose is 0.1-0.5%, and not higher than the amount of carbomer.
[0028] Furthermore, the stabilizer is a combination of one or more chelating agents such as disodium edetate, gluconic acid, and iminodiacetic acid.
[0029] Furthermore, the mass ratio of the stabilizer to the gelling agent is (0.01-0.1):0.5.
[0030] The fifth objective of this application is to provide a method for preparing a sterile dressing, comprising the following steps: Step 1: Preparation of cross-linked polyglutamic acid and cross-linked hyaluronic acid polymers First step crosslinking: Polyglutamic acid or its salt is added to an acidic matrix solution, and a crosslinking agent is added to crosslink the polyglutamic acid to obtain crosslinked polyglutamic acid; The second step is cross-linking: Hyaluronic acid or its salt is added to an alkaline matrix solution. Cross-linked polyglutamic acid is first added to the alkaline matrix solution and stirred evenly. Then, a cross-linking agent is added to cross-link the solution to obtain cross-linked polyglutamic acid and cross-linked hyaluronic acid polymers. Step 2: Prepare matrix solution A base solution is prepared by mixing polyol moisturizers, gelling agents, stabilizers, and repairing agents in a certain proportion. Step 3: Preparation of sterile dressings The polymer from step 1 is uniformly dispersed in the matrix solution from step 2 to form a transparent gel matrix. The transparent gel matrix is added to a nonwoven fabric, and sterilized to obtain a sterile dressing. Preferably, the transparent gel matrix is added to a high-temperature resistant aluminum foil bag containing nonwoven fabric.
[0031] Furthermore, in step 1, the cross-linking process of the polyglutamic acid is carried out under acidic (pH=1-3) and room temperature conditions, with a stirring time of 10-30 min and overnight standing for equilibration of 12-24 h.
[0032] Furthermore, in step 1, the cross-linking process of the hyaluronic acid is carried out under alkaline (pH=12-14) and room temperature conditions, with a stirring time of 10-30 min and overnight equilibration for 12-24 h.
[0033] Furthermore, in step 1, the physical intercalation of the cross-linked hyaluronic acid and cross-linked polyglutamic acid occurs under alkaline conditions (pH=12-14) to form a porous gel polymer.
[0034] Furthermore, in step 1, the acidic matrix can be an inorganic acid salt (hydrochloric acid or citric acid), preferably sodium citrate, and the alkaline matrix can be an inorganic base (sodium hydroxide or sodium carbonate), preferably sodium hydroxide.
[0035] The beneficial effects of this application are: (1) The cross-linked polyglutamic acid and cross-linked hyaluronic acid polymers provided in this application, wherein the cross-linked polyglutamic acid sodium gel is uniformly dispersed in the cross-linked hyaluronic acid sodium gel, and a honeycomb porous gel is formed by physical interlocking, thereby achieving the technical effect of slow release of moisture in the final product based on the porous structure.
[0036] (2) The sterile dressing provided in this application effectively solves the problem that sodium polyglutamate cannot be used alone and the sterilization problem that can be converted into mass production by combining sodium polyglutamate and sodium hyaluronate in a two-stage cross-linking method.
[0037] (3) The sterile dressing provided in this application contains a variety of repair active ingredients, which have the effects of calming and anti-inflammatory, moisturizing and hydrating and promoting barrier repair. At the same time, no preservatives are added. The product is sterile by terminal sterilization and can be used immediately after medical aesthetics and during the sensitive period of the skin. It has very high application value.
[0038] (4) The sterile dressing provided in this application contains cross-linked sodium polyglutamate and cross-linked sodium hyaluronate, which can quickly reduce redness, repair damaged skin barrier, and improve skin color, without causing irritation or secondary inflammatory reaction.
[0039] (5) The sterile dressing provided in this application can effectively improve the discomfort symptoms such as redness, heat, swelling, pain, dryness and tightness of the skin after facial minimally invasive surgery. Especially immediately after surgery, the calming and redness-reducing effect is very good, and the improvement rate of the Visia red area is significantly improved. It is derived from the porous structure formed by the cross-linking of sodium hyaluronate and sodium polyglutamate, which slowly releases water to achieve immediate water and heat exchange and calming effect. It can also slowly release and prolong the calming effect. Attached Figure Description
[0040] Figure 1 Example 1.4 Appearance (left); Comparative Example 1.1 Appearance (right).
[0041] Figure 2 Example 3: Effectiveness evaluation of facial minimally invasive surgery test. Preoperative and postoperative red area images of two volunteers. Detailed Implementation
[0042] The present application is further illustrated below with reference to embodiments. It should be understood that the embodiments are only used to further illustrate and explain the present application and are not intended to limit the present application.
[0043] Unless otherwise defined, technical and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art. While similar or identical materials and methods may be applied in experimental or practical applications, they are described herein. In case of conflict, the definitions included herein shall prevail. Furthermore, materials, methods, and examples are for illustrative purposes only and are not intended to be limiting. The present application is further described below with reference to specific embodiments, but is not intended to limit the scope of the application.
[0044] I. Main Material Sources
[0045] II. Testing Methods (1) Swelling degree test Weigh 0.5g of the sample from the examples and control examples and place it on a petri dish. Place the dish in a 40℃ oven to constant weight and record this as m1. Then place the dish in phosphate buffer to swell for 24 hours. After filtering to remove excess water, weigh the sample and record this as m2. Calculate the degree of swelling Q according to the formula.
[0046] Q= (2) Rheological test Elasticity and viscous modulus were tested using a rotational rheometer (cone angle 0.5, cone plate 60 mm, slit 0.052 mm) at a test temperature of 25℃ and a frequency range of 0.1-100Hz.
[0047] (3) Safety evaluation - cytotoxicity evaluation Referring to GB / T 16886.5-2017 "Biological Evaluation of Medical Devices" Part 5: In vitro cytotoxicity tests, the MTT assay was used to test the cytotoxicity of the examples / comparative examples, determine the effect of the samples on cell viability, and evaluate the cytotoxicity level of the samples.
[0048] Qualitative evaluation: Cytotoxic morphology, corresponding to five levels of reaction: none, slight, mild, moderate, and severe. A grade greater than 2 is considered to have cytotoxic effect. Quantitative evaluation: If the cell survival rate is less than 70% of the blank group, it indicates that the sample has potential cytotoxicity. The cell survival rate (%) = average absorbance value of the test sample / average absorbance value of the blank control group * 100%.
[0049] The specific morphological grading criteria for cytotoxicity are shown in the table below: Table of Cytotoxicity Morphological Grading Standards
[0050] (4) TEWL test method: Instrument: CK MPA 10 probe Method: Place the probe vertically against the skin test area, wait for the readings to stabilize (approximately 30-60 seconds), and record the amount of water loss per unit area per unit time (g / h·m). 2 Each area was tested three times, and the average value was taken.
[0051] (5) Test of stratum corneum moisture content: Instrument: CK Corneometer® probe (capacitance method) Method: Press the probe vertically onto the skin surface for 1 second and read the capacitance value, which reflects the degree of hydration of the stratum corneum. Measure 3 times for each area and take the average value.
[0052] (6) VISIA Red Zone Test: Using the VISIA Canfield facial imaging system, images were captured under standard and cross-polarized light. The absolute area (mm²) of the red region was analyzed using software. 2 (or feature count)
[0053] Red area improvement rate (%) = (baseline red area - post-treatment red area) / baseline red area × 100%. A positive value indicates a reduction in red area, i.e., improvement in inflammation / congestion.
[0054] Moisture content improvement rate (%) = (post-treatment moisture content - baseline moisture content) / baseline moisture content × 100%. A positive value indicates high moisture content and good moisturizing properties.
[0055] TEWL improvement rate (%) = (baseline TEWL - post-treatment TEWL) / baseline TEWL × 100%, a positive value indicates good wound repair.
[0056] Preparation Examples A method for preparing a sterile repair dressing includes the following steps: Step 1: Preparation of cross-linked sodium hyaluronate and cross-linked sodium polyglutamate polymers First step crosslinking: Weigh a certain amount of sodium polyglutamate and add it to an acidic matrix solution (pH=1-3). Add a certain amount of crosslinking agent polyethylene glycol diglycidyl ether (PEGDE) for crosslinking. Allow it to stand at room temperature for automatic equilibration crosslinking for 12-24 hours. After crosslinking is completed, adjust the pH to neutral. The second step is cross-linking: A certain amount of sodium hyaluronate is added to an alkaline matrix solution (pH=12-14). Cross-linked sodium polyglutamate gel is first added to the alkaline matrix solution and stirred evenly. Then, a certain amount of cross-linking agent, polyethylene glycol diglycidyl ether (PEGDE), is added and placed at room temperature for automatic equilibrium cross-linking for 12-24 hours. After the cross-linking is completed, the pH is adjusted to neutral, and the cross-linking agent is removed by dialysis for 1-3 days to obtain cross-linked sodium hyaluronate and cross-linked sodium polyglutamate polymer. Step 2: Prepare matrix solution A mixture of polyol moisturizer, gelling agent, stabilizer, and repairing agent is prepared in a specific ratio to form a mixed solution. The gelling agent is dispersed in the moisturizer and kept at 80-90℃ until it dissolves to a transparent state. Then, the repairing agent and stabilizer are added to obtain the matrix solution. Step 3: Preparation of sterile dressings The polymer from step 1 is uniformly dispersed in the matrix solution from step 2. Homogenization can be used to form a transparent gel matrix, which is then placed into a high-temperature resistant aluminum foil bag lined with non-woven fabric. The aluminum foil bag is then sterilized by moist heat at 121°C for 12-20 minutes or by irradiation at 5-20 KGy to obtain a sterile repair dressing.
[0057] Example 1: Preparation of a polymer of sodium hyaluronate and sodium polyglutamate Following step 1 in the preparation examples, and according to the components and proportions in Table 1, Examples 1.1-1.7, 1.A1-1.A2, 1.B1-1.B3, 1.C1-1.C2, 1.D1-1.D2, and Comparative Examples 1.1-1.2 were formed. Furthermore, the appearance of the polymers was observed, and the swelling degree, elastic modulus, and viscous modulus were tested according to the aforementioned test methods. The results are shown in Tables 1-1 and 1-2.
[0058] Comparative Example 1.1 did not use sodium polyglutamate, but only sodium hyaluronate and a crosslinking agent. The experimental procedure was the same as the second step of step 1, crosslinking. 0.5g of sodium hyaluronate (1390kDa) was added to an alkaline matrix solution (pH=12-14), mixed evenly, and then 0.2g of crosslinking agent polyethylene glycol diglycidyl ether (PEGDE) was added. The mixture was placed at room temperature for automatic equilibration and crosslinking for 12-24h. After the crosslinking was completed, the pH was adjusted to neutral, and the crosslinking agent was removed by dialysis for 1-3 days to obtain the crosslinked sodium hyaluronate polymer.
[0059] Comparative Example 1.2 is a cross-linked gel obtained by referring to steps (1) and (2) of Example CN118063833B. The specific method is as follows: A micro-cross-linked hyaluronic acid-γ-polyglutamic acid-vitamin C gel is prepared by the following method: (1) Dissolve 5g sodium hyaluronate (1390KDa) and 3g sodium γ-polyglutamic acid (1040KDa) in 15% sodium hydroxide solution (10g), stir at room temperature for 10min to obtain a homogeneous mixed solution; (2) Add 0.008mL of butanediol diglycidyl ether to the above mixed solution, and react in a 30℃ water bath for 5 hours to obtain a cross-linked product.
[0060] In Tables 1-1 and 1-2, "Low PGA" indicates low molecular weight sodium polyglutamate with a molecular weight of 216 kDa; "High PGA" indicates high molecular weight sodium polyglutamate with a molecular weight of 1040 kDa; "Ultra-High PGA" indicates ultra-high molecular weight sodium polyglutamate with a molecular weight of 2030 kDa; "HA" indicates sodium hyaluronate with a molecular weight of 1390 kDa; "PEGDE" indicates the crosslinking agent polyethylene glycol diglycidyl ether with a molecular weight of 500 Da; the unit of elastic modulus is G'(Pa); and the unit of viscous modulus is G"(Pa). These abbreviations also apply to other embodiments.
[0061] Table 1-1 Content and proportion of each component in Examples 1.1-1.7 and Comparative Examples 1.1 and 1.2
[0062] Table 1-2 Content and proportion of each component in Examples 1.4 and 1.A-1.D
[0063] This application aims to protect cross-linked polymers with porous structures, thereby achieving the technical effect of slow moisture release from the final patch product based on the porous structure.
[0064] Furthermore, based on the porous structure, this application aims to protect the cross-linked polymer with higher swelling degree. Since the higher the swelling degree, the lower the cross-linking degree, the higher the water absorption rate, and the more water is stored, the more water can be released in the final product.
[0065] Furthermore, this application aims to form a flexible cross-linked polymer, rather than a high-strength, highly cross-linked polymer gel. The cross-linked polymer in this application, combined with other gelling agents, can support the stiffness of the nonwoven fabric; therefore, a suitable elastic modulus needs to be selected. Simultaneously, considering the user's comfort when applying the product to the face, this product requires a certain degree of softness and cushioning; therefore, a suitable viscous modulus needs to be selected. The viscous modulus represents the resistance to friction during gel application; a higher viscous modulus results in a smoother feel and better skin comfort.
[0066] Based on the above analysis, the primary selection criteria for the technical solution to be protected in this application are: porous gel, small-pore gel, or low-pore gel. Further selection criteria are: the greater the swelling degree, the better; and the smaller the ratio of elastic modulus to viscous modulus, the better.
[0067] By analyzing the experimental results of each embodiment and comparative example in Tables 1-1 and 1-2, and Figure 1(The left figure is Example 1.4; the right figure is Comparative Example 1.1) It can be seen that, compared with the non-porous gel formed in Comparative Example 1.1 and the almost non-gelling non-porous mucus formed in 1.2, the technical solutions to be protected in this application (Examples 1.2-1.7, 1.A1-1.A2, 1.B2-1.B3, 1.C1-1.C2, 1.D1-1.D2) are respectively porous gels, small-pore gels, or few-pore gels, which meet the inventive purpose of this application. That is, when any high PGA, ultra-high PGA and crosslinking agent are used to crosslink and obtain crosslinked PGA, the crosslinked PGA is added to HA, and then a crosslinking agent is added to obtain the polymer, and any two or three low PGA, high PGA, ultra-high PGA and crosslinking agent are used to crosslink and obtain crosslinked PGA, the crosslinked PGA is added to HA, and then a crosslinking agent is added to obtain the polymer, all of which meet the primary inventive purpose of this application. Cross-linked sodium polyglutamate gel is uniformly dispersed in cross-linked sodium hyaluronate gel, forming a honeycomb porous gel through physical interlocking.
[0068] Furthermore, the technical solution to be further protected in this application is one with a relatively larger degree of swelling and a smaller elastic modulus / viscosity modulus ratio. Based on Tables 1-2, we can conclude that when using a combination of low PGA and high PGA, the mass ratio of low PGA to high PGA is 1:(0.25-4), preferably 2:3; the mass ratio of sodium polyglutamate to sodium hyaluronate is 1:(0.5-2), preferably 1:1. The mass ratio of sodium polyglutamate to crosslinking agent is 5:(2-5), preferably 5:3; the mass ratio of sodium hyaluronate to crosslinking agent is 5:(1-5), preferably 5:2.
[0069] Example 2: Preparation of Aseptic Dressing Following steps 2 and 3 in the preparation examples, and according to the components and proportions in Table 2, Examples 2.1-2.5 and Comparative Examples 2.1-2.2 were formed, wherein step 3 was performed by moist heat sterilization.
[0070] The crosslinked polymer used in Examples 2.1-2.5 was the same as that used in Example 1.4; the crosslinked polymer used in Comparative Example 2.2 was the same as that used in Comparative Example 1.1. Comparative Example 2.1 used a non-crosslinked polymer, i.e., 0.5 g of HA, 0.2 g of low PGA, and 0.3 g of high PGA were physically mixed.
[0071] The carbomer used in the various examples and comparative examples in Table 2 is model ETD2020NF, the sodium alginate is pharmaceutical grade, the agarose is agarose with a molecular weight of 120 kDa, "dextran 1" is a dextran with a molecular weight of 1860 kDa, and "dextran 2" is a dextran with a molecular weight of 225 kDa.
[0072] The dressings obtained in Examples 2.1-2.5 and Comparative Examples 2.1-2.2 were all sterile and qualified products when tested according to the sterility test methods in the Chinese Pharmacopoeia.
[0073] Table 2. Content and proportion of each component in Examples 2.1-2.5 and Comparative Examples 2.1-2.2
[0074] Analysis of the results of the examples and comparative examples in Table 2, as well as the arm test in the effectiveness evaluation of Example 3, reveals that Comparative Example 2.1 has a noticeable fermented polyglutamate smell, which is unacceptable to users and therefore unsuitable for use. Comparative Example 2.2 exhibits uneven gelation and inconsistent particle uniformity. Examples 2.1 and 2.4 both performed well. Example 2.2, due to its lower gel content, is generally softer. Example 2.3, with its lower ectoine content, shows a slightly weaker repair effect. Example 2.5, with its lower cross-linked polymer content, exhibits relatively weaker overall moisturizing properties.
[0075] Example 3: Evaluation of the safety and effectiveness of aseptic dressings 1. Safety evaluation (1) Cytotoxicity evaluation Following the aforementioned safety evaluation and cytotoxicity evaluation, cytotoxicity tests were performed on Examples 1.4, 2.1, and Comparative Examples 2.1-2.2. Examples 1.4 and 2.1, and Comparative Examples 2.1-2.2, were all subjected to moist heat sterilization. The cytotoxicity of Example 2.1 is representative of Examples 2.2-2.5. The qualitative and quantitative evaluation results are shown in Table 3. Table 3. Relative growth rate of each experimental group
[0076] Table 3 shows that Examples 1.4 and 2.1 exhibited grade 0 cytotoxicity, indicating no cytotoxic reaction, while Comparative Examples 2.1 / 2.2 showed grade 1 cytotoxicity, indicating slight cytotoxicity. The data indicate that the porous gel of Example 1.4 and the sterile dressing of Example 2.1 exhibited grade 0 cytotoxicity, meaning they were non-toxic to cells and highly safe; while Comparative Examples 2.1 and 2.2 both showed grade 1 cytotoxicity, indicating slight cytotoxicity. The higher cell survival rates in Examples 1.4 and 2.1 compared to the control group may be due to the porous structure formed in Examples 1.4 and 2.1, which facilitates cell migration and proliferation.
[0077] 2. Validity Evaluation (1) Arm trauma test Thirty volunteers were selected, including 25 women and 5 men, all aged between 20 and 40 years old. A disposable sterile roller was used to create a wound on the flexor side of the forearm (either arm or side) of the volunteers. The roller was 0.5 mm long and rolled back and forth once, creating a wound area of 6*6 cm. After the wound was created, the skin barrier was obviously damaged, with obvious redness, slight stinging, and a slight burning and itching sensation.
[0078] The wound area was divided into 6 parts, each 1*1cm in size, and immediately tested with a German CK skin tester to measure transepidermal water loss (TEWL) and stratum corneum moisture content. The specific testing method is as described above.
[0079] After the measurement was completed, sterile repair dressings (cut into 1*1cm squares beforehand) from Examples 2.1-2.5 and Comparative Example 2.2 were used respectively. After 10 minutes of application, the dressings were removed and the test sites were allowed to dry before testing the TEWL and stratum corneum moisture content using a German CK skin tester. The specific testing methods are as described above.
[0080] Data before and after application are shown in Table 1 (changes in stratum corneum moisture content) and Table 2 (transepidermal water loss, TEWL).
[0081] Table 4-1 Changes in stratum corneum moisture content before and after use in Examples 2.1-2.5 and Comparative Example 2.2, and the results of significance analysis.
[0082] Table 4-2 Results of Transdermal Water Loss (TEWL) and its Significance Analysis in Examples 2.1-2.5 and Comparative Example 2.2 before and after use.
[0083] Based on the changes in stratum corneum moisture content and transepidermal water loss (TWEL) of the arm wound presented in Tables 4-1 and 4-2, the following experimental results can be drawn: 1. The effects of Examples 2.1-2.5 are significantly better than those of Comparative Example 2.2. In terms of changes in stratum corneum moisture content: the improvement rate of Comparative Example 2.2 is 7.9%, while that of Examples 2.1-2.5 is 44.11%, 33.17%, 30.02%, 40.41%, and 22.11%, respectively; in terms of TWEL: the improvement rate of Comparative Example 2.2 is 4.61%, while that of Examples 2.1-2.5 is 19.83%, 12.62%, 10.53%, 15.16%, and 9.32%, respectively; 2. The effect of Example 2.1 is better than that of Examples 2.2-2.5, with Example 2.1 > Example 2.4 > Example 2.2 > Example 2.3 > Example 2.5.
[0084] These results, to some extent, demonstrate that, compared to Comparative Example 2.2, the honeycomb porous gel formed by the cross-linked sodium polyglutamate and cross-linked sodium hyaluronate polymers used in Examples 2.1-2.5 of this application has a significant and beneficial effect on the stratum corneum water content and transepidermal water loss.
[0085] Furthermore, comparing Examples 2.4 and 2.3 reveals that the difference in ectoin also caused differences in stratum corneum moisture content and moisture loss TWEL. The decrease in moisture loss TWEL reflects the increase in epidermal healing rate and barrier recovery rate, thus indicating that the repair factor (ectoin) in this application can accelerate skin barrier repair and wound healing.
[0086] (2) Postoperative testing of minimally invasive facial surgery Based on the above arm trauma results, 30 volunteers were selected. The left cheek was used as the experimental group (Example 2.1), and the right cheek was used as the control group (Comparative Example 2.2). Half of the mask was applied to both cheeks, once immediately after the procedure and once that evening; then one mask was applied daily for 7 consecutive days. Before treatment, immediately after the procedure, immediately after the mask, on the 3rd day after the procedure, and on the 7th day after the procedure, the VISIA red zone was tested, and transepidermal water loss (TEWL) and stratum corneum moisture content were measured using a CK instrument. The improvement rate (%) of the red zone, the improvement rate (%) of moisture content, and the improvement rate (%) of TEWL obtained from the VISIA red zone test were calculated. The testing methods and calculation formulas are as described above. The results are shown in Tables 5-1 (VISIA Red Zone), 5-2 (Transepidermal Water Loss (TEWL), and 5-3 (Stratum Corneum Moisture Content).
[0087] Table 5-1 Changes in the Visia red area before and after treatment and the results of significance analysis
[0088] Table 5-2 Transcutaneous water loss (TEWL) before and after treatment and its significance analysis results
[0089] Table 5-3 Moisture content before and after treatment and its significance analysis results
[0090] Analysis of the changes in the VISIA red area before and after treatment (Table 5-1) reveals that immediately after minimally invasive application, the experimental group showed a significantly higher improvement rate of 16.83% in the VISIA red area, far exceeding the 7.56% improvement rate in the control group. This difference was statistically significant in the experimental group, while no significant difference was observed in the control group. This is attributed to the porous structure of the cross-linked polyglutamic acid and cross-linked hyaluronic acid polymers in the experimental patch, which retains water and provides continuous cooling, rapidly alleviating inflammation caused by the minimally invasive procedure. By day 3, the improvement rate in the experimental group was 13.05%, a significant difference, while the control group showed only 2.6%, with no significant difference. By day 7, there was no significant difference between the two groups, suggesting the influence of the body's own repair mechanisms. In terms of improvement rate and overall results, the experimental group was significantly superior to the control group.
[0091] pass Figure 2 It was observed that after the immediate minimally invasive surgery, the photos of the red areas showed a significant increase in redness on both the left and right sides of the volunteers' faces. After the immediate application of the dressing, the redness in the experimental group (left cheek of volunteers 1 and 2) showed more significant improvement compared to the control group (right cheek of volunteers 1 and 2). After 3 and 7 days of application, the redness in the experimental group was significantly improved compared to the control group, and the repair effect in the experimental group after 7 days was even better than that in the redness before the minimally invasive surgery.
[0092] The TWEL data from the skin showed that the experimental group was superior to the control group, both immediately after application, at 3 days, and at 7 days. Immediately after application, the improvement rate in the experimental group was 49.84%, compared to 46.50% in the control group; after 3 days, the improvement rate in the experimental group was 10.92%, compared to 9.05% in the control group; and after 7 days, the improvement rate in the experimental group was 7.04%, compared to 4.21% in the control group. Although there were highly significant differences between the experimental and control groups immediately after application, the experimental group showed significantly better results than the control group at both 3 and 7 days.
[0093] The data on skin moisture content showed that both the experimental and control groups had some effect, but the experimental group had a higher improvement rate. On the 3rd day after treatment, the improvement rate of the experimental group was 14.94%, while that of the control group was 11.54%; on the 7th day after treatment, the improvement rate of the experimental group was 13.62%, while that of the control group was 11.74%.
[0094] Compared to the arm trauma test, the experimental group showed a significantly higher improvement rate in transdermal water loss (TEWL) and skin moisture content compared to the control group. However, in the facial minimally invasive surgery test, the improvement rate in TEWL and skin moisture content in the experimental group was relatively slight compared to the control group. This may be because the microcirculation speed in the face is faster, and the ingredients of the dressing on both sides of the face penetrate deeper and spread to multiple areas in all directions, resulting in a relatively slight improvement rate in TEWL and skin moisture content in the facial tests of both the experimental and control groups.
[0095] Based on the above data analysis, compared with the sterile dressing of Comparative Example 2.2, the sterile repair dressing of Example 2.1 prepared in this application can effectively improve the discomfort symptoms such as redness, heat, swelling, pain, dryness and tightness of the skin after facial minimally invasive surgery, especially the sedative and redness-reducing effect is very good immediately after surgery (e.g. Figure 2 As shown in Table 5-1), the improvement rate of the Visia red zone was significantly improved; the porous structure formed by the cross-linking of sodium hyaluronate and sodium polyglutamate slowly releases moisture, achieving immediate hydrothermal exchange and a calming effect (as shown in Tables 4-1 and 4-2), and can also slowly release to prolong the calming effect (as shown in Tables 5-1, 5-2 and 5-3); in addition, according to Examples 2.4 and 2.3, the repair factor in this application can accelerate skin healing and barrier repair, and reduce postoperative complications.
Claims
1. A cross-linked polyglutamic acid and cross-linked hyaluronic acid polymer, wherein, The polymer is a physical chimeric gel polymer formed by cross-linked polyglutamic acid and cross-linked hyaluronic acid. The cross-linked polyglutamic acid is obtained by cross-linking polyglutamic acid or its salt with a cross-linking agent, and the cross-linked hyaluronic acid is obtained by cross-linking hyaluronic acid or its salt with a cross-linking agent.
2. The cross-linked polyglutamic acid and cross-linked hyaluronic acid polymer according to claim 1, wherein, The polyglutamic acid or its salt is selected from high molecular weight (800-1500 kDa) polyglutamic acid or its salt and ultra-high molecular weight (1800-2500 kDa) polyglutamic acid or its salt, or a combination of any two or three polyglutamic acids selected from low molecular weight (200-500 kDa) polyglutamic acid or its salt, high molecular weight (800-1500 kDa) polyglutamic acid or its salt and ultra-high molecular weight (1800-2500 kDa) polyglutamic acid or its salt, preferably a combination of two or three polyglutamic acids; Further preferably, the molecular weight of the hyaluronic acid or its salt is 1000-1500 kDa.
3. A cross-linked polyglutamic acid and cross-linked hyaluronic acid polymer according to claim 1 or 2, wherein, When the polyglutamic acid or its salt is a combination of low molecular weight polyglutamic acid or its salt and high molecular weight polyglutamic acid or its salt, the mass ratio of the low molecular weight polyglutamic acid or its salt to the high molecular weight polyglutamic acid or its salt is 1:(0.25-4), preferably 2:3; Preferably, the mass ratio of the polyglutamic acid or its salt to the hyaluronic acid or its salt is 1:(0.5-2), and more preferably 1:
1.
4. A method for preparing the cross-linked polyglutamic acid and hyaluronic acid polymer according to any one of claims 1-3, wherein, The polyglutamic acid or its salt is crosslinked with a crosslinking agent to form a polyglutamic acid crosslinker. The polyglutamic acid crosslinker is added to the hyaluronic acid or its salt, and then a crosslinking agent is added to crosslink the polymer. Preferably, the crosslinking agent is a polyethylene glycol crosslinking agent, and more preferably, the crosslinking agent is polyethylene glycol diglycidyl ether.
5. The method for preparing a cross-linked polyglutamic acid and cross-linked hyaluronic acid polymer according to claim 4, wherein, The mass ratio of polyglutamic acid or its salt to the crosslinking agent in the crosslinked polyglutamic acid is 5:(2-5), preferably 5:3, and the mass ratio of hyaluronic acid or its salt to the crosslinking agent in the crosslinked hyaluronic acid is 5:(1-5), preferably 5:
2.
6. The use of a polymer according to any one of claims 1-3 or a polymer prepared by the method of claim 4 or 5 in the preparation of a dressing.
7. A sterile dressing, wherein, The dressing comprises a nonwoven fabric and a transparent gel matrix, wherein the transparent gel matrix comprises the polymer according to any one of claims 1-3 or the polymer prepared by the method according to claim 4 or 5, preferably, when the transparent gel matrix is 100 parts by weight, the polymer is 20-60 parts by weight, and more preferably, the polymer is 50 parts by weight.
8. A sterile dressing according to claim 7, wherein, The nonwoven fabric is a tensile-resistant nonwoven fabric, preferably with a breaking elongation greater than 10% in both the transverse and longitudinal directions; preferably, the transparent gel-like matrix further includes a polyol moisturizer, a repair agent, a gelling agent, and a stabilizer. Preferably, when the transparent gel matrix is 100 parts by weight, the polyol moisturizer is 3-7 parts by weight, the repair agent is 0.2-2 parts by weight, the gelling agent is 0.3-2 parts by weight, and the stabilizer is 0.01-0.2 parts by weight.
9. A sterile dressing according to claim 8, wherein, The polyol moisturizer is a combination of two or more selected from glycerin, pentylene glycol, propylene glycol, butylene glycol, and hexanediol; Preferably, the repair agent is a composition of ectoine, dextran, and allantoin; preferably, the dextran is a composition of molecules with molecular weights of 500-2000 kDa and 100-300 kDa. Preferably, the gelling agent is one or a combination of two of carbomer, agarose, xanthan gum, and sodium alginate, wherein the mass fraction of agarose is 0.1-0.5%, and not higher than the amount of carbomer used; Preferably, the stabilizer is a combination of one or more chelating agents such as disodium edetate, gluconic acid, and iminodiacetic acid; Preferably, the mass ratio of the stabilizer to the gelling agent is (0.01-0.1):0.
5.
10. A method for preparing a sterile dressing, wherein, The polymer according to any one of claims 1-3 is prepared; the polyol moisturizer, the gelling agent, the stabilizer and the repair agent are compounded into a mixed solution in a specific ratio to obtain the matrix solution; The polymer is uniformly dispersed in the matrix solution to form a transparent gel matrix. The transparent gel matrix is added to a nonwoven fabric and sterilized to obtain the sterile dressing. Preferably, the transparent gel matrix is added to a high-temperature resistant aluminum foil bag containing nonwoven fabric.
Citation Information
Patent Citations
A micro-cross-linked sodium hyaluronate gel and preparation method thereof
CN118063833B